How the Interplay Between the Commensal Microbiota, Gut Barrier Integrity, and Mucosal Immunity Regulates Brain Autoimmunity - Antonini, Martina; Lo Conte, Marta; Sorini, Chiara; Falcone, Marika (Frontiers in Immunology, 2019)
The intestinal barrier provides toward the host a strong defence line against the external environment playing also a pivotal role in the crosstalk between the gut microbiota and the immune system. Notably, increasing evidences concerning autoimmune disorders such as Multiple Sclerosis (MS), report an imbalance in both intestinal microbiota composition and mucosal immunity activation, along with an alteration of gut barrier permeability, suggesting this complex network plays a crucial role in modulating the course of autoimmune responses occurring in tissues outside the gut. Here we propose to review current knowledge on how gut inflammation and breakage of gut barrier integrity modulates the interplay between the commensal gut microbiota and the immune system and its role in shaping brain immunity.